Separation of Trace Metal as Oxoanions from Contaminated Water - Kushwah, Vandana; Kushwah, D.V.S.; Dhakad, V.S. (Asian Journal of Chemistry, 2011)
Ion exchange technique has been employed to remove trace metals from contaminated water by batch process and the ability of strongly basic anion exchanger Amberlite IRA-400 in nitrate form has been evaluated to separate chromium, molybdenum and tungstan as oxoanions viz chromate, molybdate and tungstate. Conclusions have been drawn regarding the variation of selectivity coefficient with change in solvent composition of mixed solvents such as aqueous methanol, aqueous ethanol and aqueous isopropanol. Thermodynamics of ion exchange has also been studied. The data indicates that strongly basic anion exchanger Amberlite IRA-400 in nitrate form has got good potential for separation of these oxoanions and exchange of anions increased with increase in temperature and alcoholic content. Particle size and quantity of resin also have remarkable effect on exchange.